Iron Phosphate/Bacteria Composites as Precursors for Textured Electrode Materials with Enhanced Electrochemical Properties. Issue 10 (3rd August 2016) - Mirvaux, B.; Recham, N.; Miot, J.; Courty, M.; Bernard, S.; Beyssac, O.; Davoisne, C.; Sougrati, M.; Demortière, A.; Guyot, F.; Tarascon, J. M.; Larcher, D.
Abstract : An important issue linked to the wide implementation of the Li-ion technology for large scale application deals with the development of eco-efficient synthesis processes for making electrode materials. We report herein the preparation of homogeneous, dense and nanometric layers of amorphous ferric phosphates (a-FePO4 ·xH2 O) using a bacteria ( Sporosarcina pasteurii) as nucleating template. By combining various analytical tools (including thermal analyses, Raman and XANES spectroscopies) we show that the the bacterial cell wall plays a key role in the nucleation process thereby controlling particle size and precipitation kinetics. Moreover, we demonstrate that a mild thermal treatment of the bacteria/(a-FePO4 ·xH2 O) core shell structure leads to the decomposition of the insulating bacteria into a carbon-based residue, which is beneficial to the electrode conductivity. This as-prepared material electrochemically reacts with lithium (Fe III / Fe II ) at a mean voltage of 3.0 Volts (vs. Li + /Li°) with performances (first cycle reversibility, reversible capacity, power efficiency, cycle life) that equal or even overpass those of abiotic a-FePO4 ·xH2 O materials mixed with conductive carbon through harsh or complex procedures. Overall, this bio-templating route represents a soft/cheap alternative to tackle conductivity issues in battery electrode processing.